Integration of local wisdom literacy based on flipbook worksheets to enhance students' creative problem-solving in the foundation phase of the independent curriculum - Daryati, Melia Eka; Suryadi, Didik; Wembrayarli, Wembrayarli; Hatta, Muhammad (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2024)
Background: The lack of innovative teaching materials relevant to local wisdom hinders the learning process. Flipbook worksheets serve as an innovative educational medium that effectively integrates local wisdom into instructional material delivery. This medium not only offers aesthetic appeal but also enhances interactivity, thereby fostering student engagement in reflective problem-solving activities during the learning process.Aim: The research aims to integrate flipbook worksheets enriched with local wisdom to improve students' creative problem-solving skills.Method: The study employed Research and Development (R&D) methodology, involving 40 participants, with a Likert scale used to assess student engagement.Results: The analysis yielded an F-value of 5.34 and a p-value of 0.028, indicating that the implementation of local wisdom-based flipbook worksheets has a substantively positive impact on enhancing students' problem-solving skills.Conclusion: The development of flipbook worksheets integrated with local wisdom effectively enhances students' creative problem-solving competencies. Recommendations for local wisdom-based education include integrative activities with folklore materials, visuals of traditional games, and reflective problem-solving tasks that incorporate local values such as mutual cooperation, deliberation, and responsibility.